ROLE OF CHEMICAL, BIOLOGICAL MEDICINE AND FERTILIZERS IN INCREASE OF GRAIN CROP YIELDS IN THE STEPPE PARTS OF BASHKORTOSTAN - G. N. Garipova; A. A. Sakhibgareev (Зерновое хозяйство России, 2018)
The article has presented the results of study, carried out in Preduralsky and Zauralskaya steppe zone of Bashkortostan during 2011-2015. The soil of the steppe zones was lime (calcareous) black earth (chernozem). The thermal environmental regime, the presence of moisture and nutrients in the root zone of the soil were the most essential factors in the period of vegetation. It has been established that potash and phosphate fertilizers promote the increase of grain crop resistance to diseases. It has been determined that the yield formation largely depends on the level of potential soil fertility and an amount of fertilizers. The main sources of nitrogen plant feed (ammonium and nitrate) are of equal value if there are favourable conditions for their digestion. Insufficient temperature and definite soil humidity in the early spring intensified the ammonification and there was a slight increase of ammonia in the soil till the end of tillering. All phases of the crops development were accompanied by the protection against pests using a range of measures. The efficient methods of decrease of grain crop infection by the method of seed disinfection with chemicals together with biologic drugs have been shown; the creation of tank mixtures was also an efficient method while sprinkling during the vegetation period. The groups of dangerous pests have been estimated which are the most harmful for grain crops in the steppe zones of the Republic and the measures of fighting with them have been determined.